STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN KINERJA PADA PUD. PUSAT PASAR KOTA MEDAN - Dongoran, Ranah Santri; Syahbudi , Muhammad (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research evaluates the internal and external factors that influence the performance of Medan City Market Center PUD, as well as strategies designed for human resource development based on the results of this analysis. This research uses a qualitative approach with data collection techniques in the form of interviews and documentation, while data analysis is carried out using the SWOT method. The results of the research reveal that the Medan City Market Center PUD has carried out an environmental analysis which is the basis for developing a human resource development strategy. The strategies implemented include increasing competence through training programs, adjusting organizational structures, optimizing human resources, utilizing available budgets and facilities, strengthening collaboration with stakeholders, and implementing information technology. This strategy has proven successful in supporting the achievement of optimal performance, human resource development, and increasing understanding of the quality of organizational performance at the Medan City Market Center PUD.